Analysis of Performance Differences among Students in Urban and Non-urban Centers Based on Compulsory Secondary Education Special Awards - Rocío Chao-Fernández; Francisco Jesús Ferreiro-Seoane; María Dorinda Mato-Vázquez (Revista Electrónica Educare)
This research analyzes how the teaching-learning contexts (urban and non-urban) of four provinces and their different towns influence the school performance of Galician students who apply for the compulsory secondary education (ESO, in Spanish) special award. The sample is of 1,212 students who have finished the 4th level of ESO with an average score greater than or equal to 9 between 2008 and 2012. For such purpose, we made a comparative analysis using independent samples with Levene’s test through the SPSS V. 22.0.0.0 statistical package. The results indicate that, out of the 12 scores (Galician, Spanish, foreign language, Mathematics and Social Sciences, Geography and History) and a test to choose from different options (Physics and Chemistry, Biology and Geology, Latin, Music, Technology and Arts), students from urban schools get better results in 10 of them (83.33%), with significant differences in 6 subjects.